Analisis Perilaku Harga Saham Every Month pada Perusahaan Sektor Perkebunan Sebelum dan Sesudah Peristiwa Kabut Asap pada Tahun 2016-2019 - Alma Tika Agustin; Budi Wahono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analyze a movement or reaction of share prices and trading volume before and after the haze event in plantation sector companies in 2016-2019. The population in this study are 18 oil palm plantation sector componies listed on the Indonesia Stock Exchange in 2016-2019 and the sample of this study are 7 oil palm companies that have a large of transaction values and active in the movementof stock prices for 4 years. The samples were chosen by using purposive sampling technique which samples were chosen with certain criteria. Data collection method uses secondary data, obtained by documentation by studying and analyzing a historical data of a particular company's stock. Data analysis techniques used in this research are descriptive test, normality test, and t-test. The results of the study stated that in 2016-2019 there were no significant differences in abnormal return and trading volume activity (TVA) before and after the haze event in plantation sector companies.Keywords: Abnormal Return and Trading Volume Activity (TVA)